Does capitalism have a future? - Immanuel Wallerstein (Oxford: OUP, 2013)
"The Great Recession has prompted many reassessments of the finance-driven economic order that achieved world dominance in the era of globalization. Yet just about every observer has focused on only two issues: why things went wrong, and what we need to do in order to return the system to stability. Virtually no one has questioned whether the system as such can continue. In Does Capitalism Have a Future?, a quintet of globally eminent scholars - Immanuel Wallerstein, Randall Collins, Michael Mann, Georgi Derluguian, and Craig Calhoun - survey the current global landscape and cut their way through to the most crucial issue of all: whether our capitalist system can survive in the medium run. Despite all its current gloom, conventional wisdom still assumes that capitalism cannot break down permanently because there is no alternative. The authors shatter this assumption, arguing that this generalization is not supported by theory, but is rather an outgrowth of the optimistic nineteenth-century claim that human history ascends through stages to an enlightened equilibrium of liberal capitalism. Yet as they point out, all major historical systems - from the Roman Empire to the Qing dynasty in China - have broken down in the end. In the modern epoch there have been several cataclysmic events - notably the French revolution, World War I, and the collapse of the Soviet bloc - that came to pass mainly because contemporary political elites had spectacularly failed to calculate the consequences of the processes they presumed to govern. At present, none of our governing elites and very few intellectuals can fathom an ending to our current reigning system. How possible is a systemic collapse in the medium-run of coming decades is the central question of this debate. While the contributors arrive at different conclusions, they are in constant dialogue with one another and therefore able to construct a relatively seamless--if open-ended--whole. Written by five of world's most eminent scholars of global historical trends, this ambitious book asks the biggest of questions: are we on the cusp of a radical world historical shift or not?"--
"a quintet of globally eminent scholars - Immanuel Wallerstein, Randall Collins, Michael Mann, Georgi Derluguian, and Craig Calhoun - survey the current global landscape and cut their way through to the most crucial issue of all: whether our capitalist system can survive in the medium run. Despite all its current gloom, conventional wisdom still assumes that capitalism cannot break down permanently because there is no alternative. The authors shatter this assumption,and while all of the contributors arrive at different conclusions, they are in constant dialogue with one another and therefore able to construct a relatively seamless--if open-ended--whole"--
Keywords: Capitalism; Middle Class; Technological Innovations; Capitalism; Political Science; Business Economics; Social Sciences